Benefits of medication charts provided at transitions of care: a narrative systematic review - Fine Michèle Dietrich; Kurt E Hersberger; Isabelle Arnet (BMJ Open)
Objectives Particularly at transitions of care points information concerning current medication tends to be incomplete. A medication chart that contains all essential information on current therapy is likely to be a helpful tool for patients and healthcare providers. We aimed to investigate any type of benefits associated with medication charts provided at transition points.Methods A systematic review according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was performed. Two databases, two online journals and two association websites dedicated to biomedicine and pharmacy issues were consulted to identify studies for the review using the search term ‘medication chart’ and synonyms. We run our search from database inception up to March 2019. Studies of any study design, intervention and population which examined the effect of paper-based medication charts were included. We extracted study results narratively and coded and classified them by themes and categories inductively by using the ‘framework method’ with content analysis. The methodological quality of the studies was assessed using the Effective Public Health Practice Project (EPHPP) tool.Results From the 846 retrieved articles, 30 studies met the inclusion criteria, mostly from Germany (18 studies) and the USA (5 studies). Thirteen studies reported a statistically significant result. In the ‘patient theme’, the most obvious benefits were an increase in medication knowledge, a reduction of medication errors and higher medication adherence. In the ‘interdisciplinary theme’, a medication chart represented a helpful tool to increase communication and inter-sectoral cooperation between healthcare providers. In the ‘theme of terms and conditions’, accuracy and currency of data are prerequisites for any positive effect. The quality of the studies was classified predominantly weak mainly due to unmet good quality criteria (no randomised controlled trials study design, no reported dropouts).Conclusion Overall, the reviewed studies suggested some benefits when using medication charts. Healthcare providers could consider using medication charts in their counselling practice. However, it is unknown whether the reported benefits lead to measurable improvement in clinical outcomes.PROSPERO registration number